How ancient Europeans saw the world : vision, patterns, and the shaping of the mind in prehistoric times - Wells, Peter S. (Princeton University Press, 2012)
The peoples who inhabited Europe during the two millennia before the Roman conquests had established urban centers, large-scale production of goods such as pottery and iron tools, a money economy, and elaborate rituals and ceremonies. Yet as Peter Wells argues here, the visual world of these late prehistoric communities was profoundly different from those of ancient Rome's literate civilization and today's industrialized societies. Drawing on startling new research in neuroscience and cognitive psychology, Wells reconstructs how the peoples of pre-Roman Europe saw the world and their place in it.